Screening of pediatric sleep-disordered breathing: a proposed unbiased discriminative set of questions using clinical severity scales - Spruyt, Karen; Gozal, David (Chest, 2012)
Identification of sleep-disordered breathing (SDB) using questionnaires is critical from a clinical and research perspective. However, which questions to use and how well such questionnaires perform has thus far been fraught with substantial uncertainty. We aimed at delineating the usefulness of a set of questions for identifying pediatric SDB. Random prospective sampling of urban 5- to 9-year-old children from the community and enriched for habitual snoring underwent overnight sleep study. Subjective indicators or questions were evaluated to further characterize and discriminate SDB. Of 1,133 subjects, 52.8% were habitual snorers. This sample was analyzed based on a clinical grouping (ie, established apnea-hypopnea index cutoffs). Several statistical steps were performed and indicated that complaints can be ranked according to a severity hierarchy: shake child to breathe, apnea during sleep, struggle breathing when asleep, and breathing concerns while asleep, followed by loudness of snoring and snoring while asleep. With a posteriori cutoff, a predictive score > 2.72 on the severity scale was found (ie, area under the curve, 0.79 ± 0.03; sensitivity, 59.03%; specificity, 82.85%; positive predictive value, 35.4; negative predictive value, 92.7), making this cutoff applicable for confirmatory purposes. As a result, the set of six hierarchically arranged questions will aid the screening of children at high risk for SDB but cannot be used as the sole diagnostic approach.